Upaya Meningkatkan Kemampuan Berbahasa Anak Usia Dini (4-5 Tahun) Melalui Metode Cakap - Yuliana, Siti; Agustini, Setyorini Dwi; Hamliyah, Hamliyah; Untari, Dewi; Lutfiah, Lutfiah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The development of language skills in early childhood often encounters a range of obstacles. This occurs because early childhood education frequently employs conventional teaching methods that do not sufficiently engage the children’s needs in active language use. Thus, it is necessary to develop the methods adapting to the children's needs to improve language skills in early childhood, namely the conversation method. This research aims to explain the language skills of early childhood before and after the conversation method is applied. The research design is called Classroom Action Research (CAR). In this research, there we four stages include: 1) determining the population and sample, 2) data and sources of data, 3) data collection techniques, 4) data analysis techniques. The research results show that there is an improvement in children's language skills after implementing the conversation method. This can be seen from the results of observations of teacher activities in cycle I and cycle II which have increased, from an average value of 67.40% to 83.94%. The results of observations of children's activities in cycle I and cycle II also increased, from an average value of 56.62% to 78.45%.